Tradition and Modernization. Contemporary Hungarian Popular Cinema - Balázs Varga (Images)
This article provides an overview of the recent trends and problems of Hungarian popular cinema with special regard to its cultural context outlining the process of recognition of popular cinema over the past twenty years in Hungary. In general Hungarian cinema is characterised by middle-range genres (dominantly comedy) and not by a large scope. This was the case in the 1930s and 1940s during the ’golden age’ of Hungarian comedies and popular cinema. And this typifies contemporary Hungarian popular cinema as well. However, the first decade after the political changes, the 1990s was characterised by a return to the tradition of the classical Hungarian comedies and only the 2000s brought the modernization of Hungarian popular cinema.